Pyroptosis and gasdermins—Emerging insights and therapeutic opportunities in metabolic dysfunction-associated steatohepatitis - Stoess, Christian; Leszczynska, Aleksandra; Kui, Lin; Feldstein, Ariel E. (Frontiers in Cell and Developmental Biology, 2023)
In recent years, there has been a rapid expansion in our understanding of regulated cell death, leading to the discovery of novel mechanisms that govern diverse cell death pathways. One recently discovered type of cell death is pyroptosis, initially identified in the 1990s as a caspase-1-dependent lytic cell death. However, further investigations have redefined pyroptosis as a regulated cell death that relies on the activation of pore-forming proteins, particularly the gasdermin family. Among the key regulators of pyroptosis and gasdermin D activation is the inflammasome sensor NOD-like receptor 3 (NLRP3), a critical innate immune sensor responsible for regulating the activation of caspase-1. However, a deeper understanding of pyroptosis and its interplay with other forms of regulated cell death is emerging, shedding light on a complex regulatory network controlling pore-forming proteins and cell fate. Given that cell death processes play a central role in a variety of diseases such as non-alcoholic fatty liver disease (NAFLD), steatohepatitis (NASH), autoinflammatory disorders, and cancer, and often act as a starting point in these diseases, they make appealing targets for drug development. Yet, the complete molecular mechanisms are not fully understood, and new discoveries reveal promising novel avenues for therapeutic interventions. In this review, we summarize recent evidence on pathways and proteins controlling pyroptosis and gasdermins. Furthermore, we will address the role of pyroptosis and the gasdermin family in NALFD and NASH. Additionally, we highlight new potential therapeutic targets for treating NASH and other inflammatory-associated diseases.